2006
DOI: 10.1007/s10661-006-9303-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of heavy metal contaminations in the lower Sakarya river water and sediments

Abstract: In this work, water and sediment samples were collected from three different stations located along the Sakarya river between May and September 2003. Lead, copper, chromium, zinc, nickel and cadmium concentrations were determined by using solvent extraction and flame atomic absorption spectrometric method. The results show that differences based upon sampling times, regions, sediment and water samples were observed. The mean levels of copper, nickel, chromium, lead, cadmium, zinc for sediment samples are; 4.63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 7 publications
0
15
1
Order By: Relevance
“…In the sediment there were no differences in terms of Zn, Pb, Cr, and Hg while Co and Cu accumulation level were observed significant among the months (see Tables 4 and 5). Dundar and Altundag (2007) had studied the heavy metal accumulation in sediment of Sakarya River and mean levels of copper, chromium, lead, cadmium, and zinc for sediment samples are 4.630 μg g −1 , 8.780 μg g −1 , 2.550 μg g −1 , and 9.990 μg g −1 , respectively. Akçay et al (2003) had observed that the pollution levels were significant especially for Pb, Cr, and Zn in the Gediz River and Co and Zn in the Büyük Menderes River.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…In the sediment there were no differences in terms of Zn, Pb, Cr, and Hg while Co and Cu accumulation level were observed significant among the months (see Tables 4 and 5). Dundar and Altundag (2007) had studied the heavy metal accumulation in sediment of Sakarya River and mean levels of copper, chromium, lead, cadmium, and zinc for sediment samples are 4.630 μg g −1 , 8.780 μg g −1 , 2.550 μg g −1 , and 9.990 μg g −1 , respectively. Akçay et al (2003) had observed that the pollution levels were significant especially for Pb, Cr, and Zn in the Gediz River and Co and Zn in the Büyük Menderes River.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…Zn can induce inflammatory cells and protein in lung lavage fluid and DNA synthesis in lung cells (Feng et al, 2009) and Fe, V, and Ni has been reported to be the primary determinant of acute inflammatory infection (Costa and Dreher, 1997). Pb and Cd are considered potential carcinogens (Dundar and Altundag, 2006;Massey et al, 2013) and are associated with etiology of a number of diseases, especially cardiovascular, kidney, blood, nerves, and bone diseases (Jarup, 2003). Low levels of Pb and Cd also interfere with crucial nuclear functions such as DNA replication, DNA repair and gene expression through competition with nuclear uptake, homeostasis and the function of essential metal ions (Hechtenberg and Beyersmann, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The BCR sequential extraction procedure (The European Community Bureau of Reference) provides suitable information about the bioavailability and speciation of potentially toxic elements and speciation instead of total concentration of metals [25]. The most common technique used nowadays for the determination of heavy metals in environmental and biological samples involve highly sensitive spectroscopic techniques [26], such as flame atomic absorption spectroscopy (FAAS) [27,28], inductively coupled plasma-optical emission (ICP-OES) [29] and mass spectrometry (ICP-MS) [30,31]. In this study, a sequential extraction procedure was recommended by the Standards, Measurements and Testing Programme of the European Union, for the determination of 8 heavy metals (Cd, Co, Cr, Cu, Mn, Ni, Pb and Zn) in street dust samples collected from Sakarya I.…”
Section: Introductionmentioning
confidence: 99%